Analysis of Smart Sign Board Design for Road Safety using IoT - Gopinath, B.; Porchelvi, N.; Curie, M.; Sireesha, R. M. (Journal of Ubiquitous Computing and Communication Technologies, 2022)
Traffic congestion is a major issue, particularly in urban areas where the number of vehicles on the road is continuing to rise considerably, amidst the delayed construction of road infrastructure. Researchers developed a number of traffic management systems to address this intractable issue. Despite the fact that there have been several studies on traffic management, there hasn't been enough done to examine the overall system for managing traffic on urban roads. This study aims to close the knowledge gap by providing fresh information about the current status of research into the complete Traffic Management System. The main goal is to give a comprehensive overview of the current methods suggested in the literature to address the issue of traffic congestion. Moreover, this work provides some ideas by which the road safety management can be done with the help of cloud services. As mobile technology becomes more extensively used, an evaluation approach for such smart transportation innovation strategies is explored with the help of mobile app. Therefore, based on the current research perspective, this survey offers a useful perspective on the deployment of IoT in the smart traffic management system.
Keywords: Cloud; sensors; sign boards; mobile web application